Adaptation to pH stress by Vibrio fischeri can affect its symbiosis with the Hawaiian bobtail squid (Euprymna scolopes). Issue 3 (22nd January 2020) - Cohen, Meagan Leah; Mashanova, Ekaterina Vadimovna; Jagannathan, Sveta Vivian; Soto, William
Abstract : Many microorganisms engaged in host-microbe interactions pendulate between a free-living phase and a host-affiliated stage. How adaptation to stress during the free-living phase affects host-microbe associations is unclear and understudied. To explore this topic, the symbiosis between Hawaiian bobtail squid ( Euprymna scolopes ) and the luminous bacterium Vibrio fischeri was leveraged for a microbial experimental evolution study. V. fischeri experienced adaptation to extreme pH while apart from the squid host. V. fischeri was serially passaged for 2000 generations to the lower and upper pH growth limits for this microorganism, which were pH 6.0 and 10.0, respectively. V. fischeri was also serially passaged for 2000 generations to vacillating pH 6.0 and 10.0. Evolution to pH stress both facilitated and impaired symbiosis. Microbial evolution to acid stress promoted squid colonization and increased bioluminescence for V. fischeri, while symbiont adaptation to alkaline stress diminished these two traits. Oscillatory selection to acid and alkaline stress also improved symbiosis for V. fischeri, but the facilitating effects were less than that provided by microbial adaptation to acid stress. In summary, microbial adaptation to harsh environments amid the free-living phase may impact the evolution of host-microbe interactions in ways that were not formerly considered.